Chronic Exposure to Fluoride During Gestation and Lactation Increases Mandibular Bone Volume of Suckling Rats - Interlandi, Victoria (2018)
We aimed to investigate the effect of maternal exposure to NaF on mandibular bone microarchitecture and phosphocalcic plasma parameters of the offspring. For this purpose, 10-, 15-, and 21-day-old pups (n = 6–8 per group) from two groups of mothers, control and NaF 50mg/L treated dams, were used. Plasma calcium (Ca) and phosphorus (P) levels and alkaline phosphatase activity (ALP) were measured. Fluoride concentration (F−) in bone and in stomach content was measured using potentiometry after isothermal distillation. Morphometric, histological, and histomorphometric analyses of the jaw bones were performed. Plasma Ca and P levels and ALP activity increased in 10-day and decreased in 21-day-old pups from NaF-treated mothers. Fluoride concentration in stomach content samples of 15- and 21-day-old nursing pups from mothers exposed to NaF in their drinking water was higher compared to that observed in control dam offspring. Mandibular F− content was higher in 21-day-old pups born to F−-exposed dams compared to those observed in age-matched control pups. Mandibular area increased in 21-day-old pups born to treated mothers as compared to controls. Mandibular bone volume BV/TV (%) was higher in offspring from NaF-exposed dams than in controls at all the studied times. The increase in bone volume after exposure to F− was concomitant with the increase in trabecular thickness and the decrease in trabecular separation. Altogether, our results showed that exposure to NaF during gestation and lactation increased mandibular area and bone volume of pups, with concomitant changes in phosphocalcic parameters associated with the bone modeling process.